Multidisciplinary management of endocrinopathies and treatment‐related toxicities in patients with Bloom syndrome and cancer. Issue 2 (23rd November 2020) - Fein Levy, Carolyn; Presswala, Lubaina S.; Slomovic, Alana; Stiefel, Jessica; Schulman‐Rosenbaum, Rifka
Abstract: The treatment of malignancy in cancer predisposition syndromes that also confer exquisite sensitivity to standard chemotherapy and radiation regimens remains a challenge. Bloom syndrome is one such disorder that is caused by a defect in DNA repair, predisposing to the development of early‐onset age‐related medical conditions and malignancies. We report on two patients with Bloom syndrome who responded well to chemotherapy despite significant alterations to standard protocols necessitated by hypersensitivity. Both patients experienced severe toxicities and exacerbation of endocrine comorbidities during chemotherapy. A multidisciplinary team of oncologists and endocrinologists is best suited to care for this patient population.